PROBLEMATIKA MANAJEMEN KELEMBAGAAN PENDIDIKAN ISLAM DI INDONESIA - Mansir, Firman (Jurnal Manajemen Pendidikan, 2025)
This article describes various issues that have not been resolved in the context of setting up an Islamic educational institution, especially in Indonesia. Islamic education management as a branch of management is very important to be an instrument in the process of Islamic education institutions. It plays an important role for Muslim scientists, scholars and government as the best and ethical learners. In this country, Islamic education expeditions have gone through various trajectories of time, starting from before the independence to the modern era. Through the trajectory of time that has passed, there are various educational institutions that cover Islamic religious education. This study uses a qualitative approach. Therefore, in the data analysis, literature studies were carried out from various sources, both articles from international and national journals as well as research books relevant to this research issue. In the course of Islamic education experienced various obstacles and trials from various elements. The problems of management and institutions of Islamic education in Indonesia. The importance of knowledge in life so that it is necessary for every human being to be sensitive to various issues, especially in the world of education and Islamic education. This is done so that education in Indonesia can continue to improve in the future.